2003
DOI: 10.1016/s0014-4886(03)00139-0
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor deficits in a unilateral intrastriatal 6-OHDA partial lesion model of Parkinson's disease in marmoset monkeys

Abstract: Animal studies investigating the efficacy of neurotrophic factors as treatments for Parkinson's disease (PD) ideally require partial dopamine (DA) lesion models. The intrastriatal 6-hydroxydopamine (6-OHDA) lesion model may be suitable for this purpose. Although this model has been well characterized in rodents, it has not previously been used in monkeys. The goal of the present study was to characterize the behavioral effects of unilateral injections of 6-OHDA in the basal ganglia of common marmoset monkeys (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 61 publications
1
32
0
2
Order By: Relevance
“…The injections were made using coordinates derived from the stereotaxic atlas of Stephan et al (1980) at the following sites: (1) In experiment 2, the monkeys in group GDNF plus LES and group GFP plus LES underwent the intrastriatal 6-OHDA surgery 8 weeks after the vector surgery. In a previous study, we found that nine intrastriatal injections of 8 g each of 6-OHDA resulted in behavioral deficits that recovered by 10 weeks after lesion (Eslamboli et al, 2003a). In the hope of achieving longer-lasting behavioral deficits, twice as many injections were made into the striatum between coordinates AP6.5 to AP13.5, LAT2.3 to LAT6.7, and V8.5 to V13.2 (i.e., a total of 18 injections of 8 g each of 6-OHDA).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…The injections were made using coordinates derived from the stereotaxic atlas of Stephan et al (1980) at the following sites: (1) In experiment 2, the monkeys in group GDNF plus LES and group GFP plus LES underwent the intrastriatal 6-OHDA surgery 8 weeks after the vector surgery. In a previous study, we found that nine intrastriatal injections of 8 g each of 6-OHDA resulted in behavioral deficits that recovered by 10 weeks after lesion (Eslamboli et al, 2003a). In the hope of achieving longer-lasting behavioral deficits, twice as many injections were made into the striatum between coordinates AP6.5 to AP13.5, LAT2.3 to LAT6.7, and V8.5 to V13.2 (i.e., a total of 18 injections of 8 g each of 6-OHDA).…”
Section: Methodsmentioning
confidence: 94%
“…GDNF expression at 0.04 ng/mg of tissue did not affect normal DA neurotransmission, so an rAAV expressing this amount was used in a recently developed intrastriatal 6-hydroxydopamine (6-OHDA) lesion (LES) model of PD in monkeys (Eslamboli et al, 2003a). This low level of GDNF expression in the striatum provided substantial protection of the nigrostriatal DA system and functional recovery on a range of behavioral measures.…”
Section: Introductionmentioning
confidence: 99%
“…Following unilateral these novel therapies will be discussed in more detail later in this review. lesions, asymmetrical rotation can be observed spontaneously in rats, or in response to dopaminergic drugs 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine such as amphetamine, apomorphine, and levodopa (30,52). This rotational analysis has been important for the First discovered to produce parkinsonian effects in human drug users (63), 1-methyl-4-phenyl-1,2,3,6-tetrabehavioral quantification of lesion severity as well as providing a measurement of therapy-induced recovery.…”
mentioning
confidence: 99%
“…Figure 5 Maximum weight pulled by individual female and male marmosets relative to body weight during baseline period Eslamboli et al 2003) rather than measuring muscle function per se.…”
Section: Female Malementioning
confidence: 99%
“…As well as investigating toxicological effects of compounds on muscle function, the technique has potential to improve the characterization of marmoset models of human disease. These could include models of Parkinson's disease (Henderson et al 1998, Eslamboli et al 2003), Huntington's disease (Kendall et al 2000) and the muscle-weakening effects of stroke (Marshall et al 2000) and could, of course, be scaled up for applications using larger species of non-human primates.…”
Section: Female Malementioning
confidence: 99%